PENGARUH MODEL PEMBELAJARAN GROUP TO GROUP EXCHANGE BERBANTUAN HANDOUT TERHADAP HASIL BELAJAR IPA BIOLOGI - Arnidar Hondro; Afdal Saputra; Murhati Sarumaha (TUNAS : Jurnal Pendidikan Biologi, 2023)
The purpose of carrying out this research is to determine the effect of the Group to Group Exchange learning model assisted by handouts on the science-biology learning outcomes of class VIISMP Private Imanuel Teluk in the 2022/2023 academic year. This research uses a quantitative approach with a quasi-experimental method. The population of this study were all students in class VII of Imanuel Telukdalam Private Middle School. The sample for this research was class VII-1 with a total of 20 students and class VII-2 with a total of 18 students. The instrument used is a learning outcomes test which is divided into two, namely initial test and final test and documentation. Based on the results of data processing that has been carried out and hypothesis test calculations, tcount = 2.35 and ttable = 1.69. This shows the value of tcount ttable, then Ho is rejected and Ha is accepted, so it can be concluded that there is an influence of the Group to Group Exchange learning model assisted by Handouts on the Biology Science learning outcomes of class VIISMP Private Imanuel Teluk in the 2022/2023 Academic Year. Some suggestions are: (1) Science-Biology subject teachers should apply the Group to Group Exchange learning model with the help of Handouts in accordance with the theoretical basis for carrying out the learning process; 2) students are expected to be more active in learning so as to obtain very satisfying results; 3) The results of this research should be used as comparison material for future researchers.